1999
DOI: 10.1016/s0735-1097(99)00421-0
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of childhood hypertrophic cardiomyopathy

Abstract: High-dose beta-blocker therapy improves survival in childhood HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Some may improve with high-dose b blockers. 45 Surgical relief of the symptomatic person with obstructive cardiomyopathy may be successful and an occasional patient has undergone cardiac transplantation.…”
Section: The Heartmentioning
confidence: 99%
“…Some may improve with high-dose b blockers. 45 Surgical relief of the symptomatic person with obstructive cardiomyopathy may be successful and an occasional patient has undergone cardiac transplantation.…”
Section: The Heartmentioning
confidence: 99%
“…[1,8,9,12,13] Symptomatic improvement persists in about 70% needed, as treatment with a high dose of a β-blocker is often of patients for at least 5 years after the operation. [8,9,12,13] Reported required for the alleviation of symptoms, but may also have complications include perioperative ventricular septal defect, third prognostic merit in children; [6] thus β-blockers should be preferred degree AV block requiring pacemaker implantation, cerebral emas the first choice of treatment. The propranolol dose can start at bolism, and left bundle branch block apparent in almost 40% of 1.5-3 mg/kg/day, and be increased gradually to a minimum of 6 patients treated postoperatively.…”
Section: Medical Treatment In Obstructive Hcmmentioning
confidence: 99%
“…[14,15] Intraoperative transesophageal echocardiography given to children with bronchospasm or hypoglycemia. [6] provides exact measurement of the septal thickness after the Verapamil should be used with caution in children with LVOT resection, as well as the residual gradient, so as to guarantee obstruction, as it can possibly lead to peripheral vasodilatation and adequate excision and prevention of ventricular septal defect. [14] serious hemodynamic complications.…”
Section: Medical Treatment In Obstructive Hcmmentioning
confidence: 99%
“…Reduced coronary vasodilator reserve (CVR) is one of the causes of these associations, even among patients with angiographically normal coronary arteries (2). Reduction in CVR leads to precipitation of myocardial ischemia and remortality rate has been reported in patients with these conditions (6,7,10). However, another study has reported that the mortality rate in HCM is not particularly high (11).…”
Section: Introductionmentioning
confidence: 99%